Disseminated mucormycosis: An unusual case of ascites with bone marrow invasion. (2022) - Sami, Chowdhury Adnan; Rashed, Hasan Mostafa; Khan, Abed Hussain; Barai, Lovely; Arafat, Shohael Mahmud
Abstract: Mucormycosis is a fatal invasive illness most frequently seen in immunocompromised hosts with uncontrolled diabetes, hematological malignancies, organ transplantation, or long-term steroid treatment. It has a poorer outcome than other fungal diseases due to its rapid spread and resistance to antifungal agents. We report a rare case of disseminated mucormycosis including the bone marrow, peritoneum, lung, and lymph nodes in an apparently immunocompetent 58-year-old gentleman who presented with two months of ascites and weight loss. After a thorough analysis, we found aseptate fungal hyphae in the bone marrow and ascitic fluid. In addition, a cottony white, woolly growth indicative of mucor species was seen in the ascitic fluid culture. CT scans of the chest and abdomen indicate characteristics consistent with mucor invasion. We began the patient on tablet posaconazole, but he died on the fifth day. The atypical presentation in an apparently immunocompetent patient and broad dissemination with rare bone marrow involvement emphasizes the disease's invasiveness.